Trends of Sports in Tourism Research Publications: Bibliometric Analysis - Sri Rizki Handayani; Amung Ma'mun; vanessa Gaffar; Mustika Fitri; Aldilla Yulia Wiellys Sutikno (Universitas Negeri Semarang, 2025)
Bibliometric analysis study of published research subjects to see the trend of the number of publications, citation trends, journals with the most publications, researcher trends, and network visualization, overlay visualization and density visualization on the topic of sports in tourism. This research design is in the form of a content analysis based on an Internet search conducted using the Dimensions application, with VOSviewer software, version 1.6.20. The flowchart is used as a reporting item for systematic reviews and meta-analyses (PRISMA), with step 1 (identification) stage 2 (screening), stage 3 (study eligibility), scopus database taken from 2015 to 2024. Which publications on sports in tourism from year to year increase, then, network visualization identifies areas that emerge from the research domain, namely sports are connected to tourist activity, but sports are not connected to active sport tourism. Thus, novelty for further research on the topic of sports in tourism can be obtained through research on sports associated with active sport tourism. Overlay visualization to see current research trends are yellow terms. For example, recreational sport, sport tourism industry. Furthermore, the visualization of the research density level is shown around the yellow dot, which means that the topic has been widely used in previous research such as sports events, tourism industry, conversely, low weight and density are around the blue dot, which means that the topic is still little used in previous research such as active sport tourism and event tourism. The conclusion, level of scientific article publication shows significant development as seen from the increasing graph from year to year. Likewise, article citations also show an increase.